2014
DOI: 10.1002/pon.3637
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics and effectiveness of Question Prompt List interventions in oncology: a systematic review of the literature

Abstract: Question Prompt List interventions are effective in improving communication, psychological and cognitive outcomes of cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
188
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(197 citation statements)
references
References 41 publications
2
188
1
1
Order By: Relevance
“…Acting on these findings, it was decided to include QPL use in the physician course curriculum. We are confident that this favored adherence to this recommendation also because the most recent evidence in the field suggests that the effects of QPLs are greater if training is offered to professionals on addressing them during the consultation and encourage patients to use them [35].…”
Section: Discussionmentioning
confidence: 86%
“…Acting on these findings, it was decided to include QPL use in the physician course curriculum. We are confident that this favored adherence to this recommendation also because the most recent evidence in the field suggests that the effects of QPLs are greater if training is offered to professionals on addressing them during the consultation and encourage patients to use them [35].…”
Section: Discussionmentioning
confidence: 86%
“…We also assessed acceptability by determining the effect of the intervention on interaction length because significantly increasing interaction length might reduce feasibility in clinical settings. Findings from prior studies evaluating the effect of QPLs on interaction length have been mixed, with most suggesting no significant effects[35, 37, 86]. Thus, we expected neither format to significantly increase interaction length.…”
Section: Introductionmentioning
confidence: 86%
“…The intervention was a question prompt list (QPL), a list of questions related to a medical condition that patients might want to ask their physician during clinic visits. QPLs are designed as a simple, inexpensive way to help patients gain more information about their diagnosis and treatment and enhance patient-provider communication[3538]. Although QPLs have been used successfully in several oncology settings[31,39,40], they have not, as far as we know, been evaluated in the context of racially-discordant oncology interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the new consult decision aid should stimulate patient–clinician discussion within the consultation on the options, prompt them to consider other information tailored to the patient’s personal situation, provide the patient opportunities to ask other questions; for example, how does this new medication fit with their other medications and health conditions (e.g., allergies), plus discuss possible side effects and ways they could be managed. A systematic review has indicated that question prompt lists are effective interventions for improving communication and cognitive outcomes [36]. …”
Section: Discussionmentioning
confidence: 99%